Implementation of Community-Based Development Programs in Disadvantaged Areas: Challenges and Successes - Wahyudi Mokobombang (Digital Innovation : International Journal of Management, 2024)
This study presents a case study on the implementation of community-based development programs in disadvantaged areas, focusing on the challenges and successes encountered during the execution of these initiatives. Utilizing a qualitative approach, the research involved in-depth interviews with various stakeholders, including community members, local government officials, and representatives from non-governmental organizations. The findings indicate that community engagement in the development process not only enhances the effectiveness of the programs but also strengthens the sense of ownership and responsibility among residents. However, the study also identifies several challenges, such as limited resources, inadequate infrastructure, and resistance to change, which can hinder progress. These findings underscore the importance of a collaborative approach and sustained support from all stakeholders to achieve success in community-based development. Furthermore, the research highlights the necessity of tailoring programs to meet the specific needs and contexts of the communities involved. This study provides valuable insights for policymakers and practitioners in designing and implementing more effective development programs in disadvantaged areas, emphasizing the critical role of community participation in fostering sustainable development.